醫乃仁術: 儒家視野下的醫患關係: The Physician-Patient Relationship: A Confucian Revision - WANG, Jue (International Journal of Chinese & Comparative Philosophy of Medicine, 2009)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文首先廓清了“醫乃仁術”在傳統儒家思想脈絡裏的含義，並指出從來源上說，它迥異於西方生命倫理學主流，而採取了一種獨特的“不離人倫，親親為本”的視角。然而這種視角使得“醫乃仁術”總是被一種歧義所困擾：它既是一種行善原則，也是一種未顧及自主性原則的行善原則，家長主義的陰影無處不在。“醫乃仁術”的歧義成為中國生命倫理學建設的最大瓶頸。面對這種困境，本文試圖在現代西方生命倫理學話語實踐之外，另闢蹊徑，借助關懷倫理學和美德倫理學的最近研究成果，闡發“醫乃仁術”的合理內涵。 This essay addresses the ethical implications of the physician-patient relationship from the Confucian perspective, which holds that the physician must regard the patient as a family member to treat the patient properly. It is well known that there are two primary approaches to moral authority in contemporary Western medical ethics. One is internal, and assumes that the good inherent to medicine is the source of moral authority in medical activities. The other is external, and denies that the ends and ethics of medicine can be determined by typical medical activities. It holds that medical ethics should be based on general moral principles, such as autonomy and justice. However, the Confucian model seems to be at odds with both of these approaches. On the one hand, Confucians do not think that medicine constitutes a self-contained domain of activity with its own ethics; rather, medicine is seen as a continuum of familial relationships and ethics. On the other hand, Confucians also hold that the physician-patient relationship should follow the example of the flexible relationships among family members rather than the rigid general principles of autonomy and justice. The Western model is aimed at action, whereas the Confucian view focuses on personal affective relations. The greatest problem with the Confucian model is its notorious paternalism; that is, it appears to fail to pay sufficient attention to the potential conflict between patient and physician about the good, ignoring the issue of patient autonomy. In the modern Western tradition, the model of the physician-patient relationship is based on two self-sufficient agents (patient and physician) who are united in pursuing a certain good, where each is the final source of what is good for him- or herself. However, the real physician-patient encounter demands a deeper commitment between the two than this model suggests. When entering a physician-patient relationship, what the patient seeks is care from the physician, not autonomy. That is to say, the patient first of all trusts the physician. To earn that trust, it is not enough that the physician treat the patient based only on the principle of autonomy or what the patient requires. Rather, a deep attachment – analogous to a familial relationship – must be developed that can serve as the basis of the encounter between the patient and physician. The Confucian physician-patient model, which is rooted in such a relationship, does not contrast but rather complements its Western counterpart. DOWNLOAD HISTORY | This article has been downloaded 564 times in Digital Commons before migrating into this platform.